Healthy lifestyle counseling, and barriers perceived by general practitioners in Poland - Znyk, Małgorzata; Kaleta, Dorota (Frontiers in Public Health, 2023)
Introduction The aim of the study was to determine the influence of the personal factors, such as body mass index (BMI), of general practitioners (GPs), and their counseling on weight management, healthy lifestyle, and their perceived barriers. Materials and methods The cross-sectional study was conducted from January 2020 to December 2021 among 161 GPs in the city of Lodz. Results Only 3.7% of physicians always advised their patients on diet and physical activity (p < 0.05). Most of the GPs (54%) provide counseling occasionally. GPs gave general advice more often to patients with chronic diseases than to patients who did not. The study showed that the chance of providing advice on eating habits or physical activity was significantly higher for the GPs who practiced physical activity (OR = 2.64; 95%Cl: 1.01–6.91, p < 0.05) and measured patient weight, height, and BMI (OR = 4.86; 95%Cl: 1.86–12.67, p < 0.001). GPs who were overweight (OR = 3.55; 95%Cl: 1.49–8.41, p < 0.01) and measured patient weight, height, and BMI (OR = 3.61; 95%Cl: 1.58–8.25, p < 0.01) were more likely to advise on nutrition or physical activity to “healthy” patients. Doctors who measured patient weight, height, and BMI advised patients with chronic diseases (OR = 6.45; 95%Cl: 2.54–16.34, p < 0.001). Over 40% of GPs believe that they are not effective in counseling. Lack of time turned out to be the main barrier to counseling for 73.3% of GPs, which was associated with heavy workload (>100 visits per week). Conclusion As many GPs doubt their effectiveness, it is recommended that GPs attend more training activities regarding counseling. In addition, organizational changes are needed to reduce patient numbers, and financial incentives are needed to improve counseling and patient measurement.